Governan??a relacional na governan??a de terceiriza????o de servi??os de TI de uma empresa p??blica brasileira: um estudo explorat??rio - Neves, Rodrigo Galisa (2018)
IT Outsourcing (ITO) in the public sector is a constantly growing management practice, but a significant part of outsourcing agreements still fails or suffers serious problems. ITO is far from an easy-to-run practice. In recent years, ITO has changed from a formal contract-based practice - contractual governance - to a relationship-based practice - relational governance - and the ITO literature in the public sector reveals that quality of the relationship is an important success factor. However, specific studies on this subject are rare in the literature. In this context, this exploratory study aimed to analyze the outsourcing governance of IT services in a Brazilian public company, investigating aspects of relational governance present in the relationship between a public-sector customer and private-sector suppliers. For this purpose, a literature review was conducted on ITO governance (focused on relational governance) and international standards were analyzed on the theme of outsourcing and collaborative relationships. Questionnaires and interviews with managers of the public organization. A manager of an IT supplier company was interviewed. The results showed that relational governance plays an important role in the execution and success of ITO agreements in the public sector. However, some precautions must be taken to avoid excessive use of relational aspects that could put companies at risk. The results of this work support the understanding of previous research on bureaucracy and restrictions related to the public sector, which makes relations between public clients and private IT suppliers more complex. In these circumstances, the use of relational governance, risk-weighted, is even more important for the success of the agreements.